DETERMINAN PRODUKSI DAN KEUNTUNGAN USAHATANI CABAI MERAH BESAR DI KECAMATAN WAY SULAN KABUPATEN LAMPUNG SELATAN - Hutapea, Evita Natasya; Arifin, Bustanul; Abidin, Zainal (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
This research aims to analyze the factors that influence productivity and the profitability of large red chili farming in Way Sulan District. This research used a survey method and was carried out in Way Sulan Subdistrict, South Lampung Regency in March - April 2019. The 56 respondents were selected using a simple random sampling method. The first objective was analyzed using the Cobb-Douglas production function with variables namely NPK fertilizer, SP36 fertilizer, insecticide, fungicide, herbicide, labor, and seed on the productivity of large red chilli farming. The second objective was analyzed by the analysis using the UOP or Cobb-Douglas profit function, which is a derivative of the production function but normalized by the output price. The study suggests that the productivity of large red chili farming was determined by NPK fertilizer, SP36 fertilizer, fungicide, labor which can increase the productivity. The second result suggests that the profit function of large red chili farming is influenced by land size, NPK fertilizer price, and labor wages that are normalized with output prices significantly and can increase the profit of large red chili production. Key words: production, profit, red chili